Effect of Consortia and Mono Inoculants of Rhizobium sp. and PGPR on Productivity of Urdbean (Vigna mungo L.), Soil Health and Profitability - Neha Joshi; Ramesh Chandra; Navneet Pareek (Journal of the Indian Society of Soil Science, 2023)
Combined inoculation of Rhizobium sp. and plant growth promoting rhizobacteria (PGPR) is now advocated in pulse crops for the maximization of nitrogen (N) fixation, plant growth and yield. However, seed treatment with separate inoculants of both rhizobia and PGPR is difficult due to limited seed surface and cumbersome activity. Therefore, a field study was conducted during kharif season of 2019 to compare the seed inoculation efficacy of different consortia inoculants of two Rhizobium sp. (PUR-34 and A-3) and two PGPRs (Stenotrophomonas rhizophilia PUK-171 and Nanobacterium sp., PUK-46B6) and their mono inoculants on nodulation and productivity of urdbean, soil properties and profitability. The used Rhizobium sp. and PGPRs organisms indicated synergistic interaction under cultural conditions. Inoculation of different consortia inoculants of Rhizobium sp. and PGPR significantly increased the nodule number and nodule dry weight over the uninoculated control. These treatments also gave significantly more plant dry weight at 45 and 60 days after sowing (DAS). Different consortia inoculants increased the grain yields ranging from 27.4 to 35.1 per cent over the uninoculated control and 8.6 and 15 per cent over the recommended dose of fertilizer (RDF) treatment. However, they were statistically comparable to their respective mono-inoculants. Consortia inoculants were found significantly superior to their mono inoculants in improving available N and phosphorus (P) and enzyme activities in soil at harvest. Consortia inoculant of PUR-34 + PUK-46B6 was found superior to others by registering maximum yield, net return and B:C ratio.